The Hidden Health Crisis: Microplastics and Their Medical Consequences - Roman, Jakub; Gondko, Daniel; Dębiec, Patrycja; Pietrzak, Nikodem (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Microplastics, ubiquitous environmental contaminants, are increasingly recognized for their potential to impact human health. This review aims to consolidate existing knowledge on the pathways through which microplastics interact with biological systems and to elucidate their health implications. State of Knowledge: Microplastics are pervasive in various environments, from aquatic to terrestrial ecosystems, and they eventually enter the human body via ingestion, inhalation, or dermal absorption. Studies have suggested that microplastics carry toxic substances, such as heavy metals and organic pollutants, which are known endocrine disruptors and carcinogens. Additionally, the physical presence of microplastics has been linked to inflammation and other negative health outcomes. Research in this field is complex and interdisciplinary, involving toxicology, environmental science, and public health disciplines. Summary: The presence of microplastics in the human body is concerning, and there is a clear need for further research to understand the extent of health risks associated with chronic exposure. Public health strategies should include both reducing microplastic pollution and strengthening regulations on plastic waste. Meanwhile, medical professionals should consider the potential for microplastic exposure when diagnosing and treating chronic conditions. Future research should aim to clarify the mechanisms of toxicity and establish safe levels of exposure, with a multidisciplinary approach being essential for comprehensive understanding and effective intervention.